2015
DOI: 10.1364/ao.54.005797
|View full text |Cite
|
Sign up to set email alerts
|

Two-frequency mutual coherence function for Gaussian-beam pulses propagating along a horizontal path in weak anisotropic atmospheric turbulence

Abstract: A theoretical formulation of the spherical-wave two-frequency mutual coherence function (MCF) for a propagation path characterized by a complex ABCD matrix with anisotropic atmospheric turbulence existing somewhere is developed. A specialization of this formulation leads to an expression for the two-frequency MCF of an equivalent pulsed Gaussian beam propagating in weak anisotropic atmospheric turbulence along a horizontal line-of-sight path; relevant closed-form analytical solutions under both near- and far-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…However, there are experimental observations demonstrating the existence of statistical anisotropy of the turbulence in some portions of the atmosphere (see, e.g., [16], [17]). It has been shown that the anisotropy of the turbulence has an important impact on optical-wave propagation [18], [19]. In fact, the wave field of the spatial-mode states in the Hadamard basis may feature a non-circularly-symmetric pattern, viz., may exhibit obvious direction-dependence (see, e.g., Fig.…”
Section: Average Probability Of Detecting a Photon Prepared In Hadamard Basis With Standard Basis Used As Measurement Basismentioning
confidence: 99%
See 3 more Smart Citations
“…However, there are experimental observations demonstrating the existence of statistical anisotropy of the turbulence in some portions of the atmosphere (see, e.g., [16], [17]). It has been shown that the anisotropy of the turbulence has an important impact on optical-wave propagation [18], [19]. In fact, the wave field of the spatial-mode states in the Hadamard basis may feature a non-circularly-symmetric pattern, viz., may exhibit obvious direction-dependence (see, e.g., Fig.…”
Section: Average Probability Of Detecting a Photon Prepared In Hadamard Basis With Standard Basis Used As Measurement Basismentioning
confidence: 99%
“…This may arouse one's curiosity about whether anisotropy of turbulence plays a role in decaying the mutual unbiasedness of complementary bases relevant to propagated photonic spatial-mode states. To deal with this issue, below we choose a turbulence spectrum taking the following form [18]…”
Section: Average Probability Of Detecting a Photon Prepared In Hadamard Basis With Standard Basis Used As Measurement Basismentioning
confidence: 99%
See 2 more Smart Citations
“…Obviously, atmosphere is one of the important factors that cause the distortion of optical signals. It will lead to the phenomena such as irradiance scintillation, beam drift, beam expansion and arrival angle fluctuation [2]. If the strong turbulence cannot be detected, the spot information of light field is too difficult to be calculated.…”
Section: Introductionmentioning
confidence: 99%